Gaya Humor terhadap Optimisme Mahasiswa yang Sedang Menyelesaikan Skripsi - Andi Muskerina; Kurniati Zainuddin; Ahmad Ridfah (Philanthropy: Journal of Psychology, 2018)
The collage students who accomplish the undergraduate thesis will face many demands and obstacles and lead them to some difficulties if they perform low optimism. The aim of this study was measuring the relationship between humor style and optimism among the Engineering students at State University of Makassar who accomplish the undergraduate thesis. The participants of this study were 231 collage students from Engineering Faculty at State University of Makassar. Sampling technique used in this study was accidental sampling with quantitative method. The result of this study showed that affiliative humor style positively related to optimism (r=0,314,p=0,000), self enhancing humor positively related to optimism (r=0,155,p=0,018), aggressive humor negatively correlated with optimism (r=-0,324,p=0,000), and self-defeating humor negatively correlated with optimism (r=-0,163,p=0,013). This study proved that affiliative humor and self-enhancing humor can increase the optimism. In contrast, aggressive and self-defeating humor can diminish the optimism among the students.